2021
DOI: 10.1017/s0144686x21000453
|View full text |Cite
|
Sign up to set email alerts
|

Functional difficulties and toileting among older adults in Ghana: evidence from the World Health Organization Study on global AGEing and adult health (SAGE) Ghana Wave 1

Abstract: Ghana's older population is projected to increase in coming decades and as a result will see increasing care needs. Understanding the functional difficulties older adults experience, and the associated factors, will help identify relevant intervention to assist older adults in meeting their care needs. This study aimed to analyse the prevalence of functional difficulties among older adults in Ghana, and examine how the World Health Organization International Classification of Functioning, Disability and Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…As such, our evidence does not describe current phenomena and may not be applicable in situations where evidence from current data is needed. Yet, this study is one of several recently published studies [ 15 , 23 , 24 , 25 ] utilizing data of a similar age. Moreover, it has provided evidence and methods that can encourage or inform future research.…”
Section: Discussionmentioning
confidence: 99%
“…As such, our evidence does not describe current phenomena and may not be applicable in situations where evidence from current data is needed. Yet, this study is one of several recently published studies [ 15 , 23 , 24 , 25 ] utilizing data of a similar age. Moreover, it has provided evidence and methods that can encourage or inform future research.…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, available quantitative research has reported that some older adults experience poor health, difficulty in participating in household activities, and limited social gathering participation (Amosun et al., 2013; Debpuur et al., 2010). A recent study also reported that about 26% of older adults experience toileting difficulty (Awuviry‐Newton et al., 2019; Awuviry‐Newton, Wales, et al., 2021), and about 31% experience transportation difficulty (Awuviry‐Newton, Ofori‐Dua, et al., 2021). The prevalence of the aforementioned functional difficulties is higher among older women than among older men (Awuviry‐Newton, Ofori‐Dua, et al., 2021; Awuviry‐Newton et al., 2020; Debpuur et al., 2010).…”
Section: Introductionmentioning
confidence: 95%
“…This finding implies that health factors better moderate the relationship between housing and long-term care needs. Health-related factors determining the significant association between housing and long-term care needs, as revealed in this study, are not surprising because older adults living with multiple chronic conditions will have more functional disabilities [14,33]. that may increase their needs for long-term care.…”
Section: Discussionmentioning
confidence: 63%
“…As defined by the WHO Joint Monitoring Programme (WHO-JMP) [28], when all four variables met the criteria for improvement (detail given below), overall housing quality was considered as improved [29,30]. In this study and similar to Awuviry-Newton, Wales, Tavener, Kowal, Byles [14], we decided to measure the effects of the four separate variables on the longterm care needs of older adults, rather than using the overall measure of housing quality. This technique is relevant because it enlightens the unique impact and quantum of association on long-term care.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation